Development of Bio-Machine Based on the Plant Response to External Stimuli - K. Aditya; Ganesha Udupa; Yongkwun Lee (Journal of Robotics)
In the area of biorobotics, intense research work is being done based on plant intelligence. Any living cell continuously receives information from the environment. In this paper, research is conducted on the plant named descoingsii x haworthioides (Pepe) obtaining the action potential signals and its responses to stimulations of different light modes. The plant electrical signal is the reaction of plant’s stimulation owing to various environmental conditions. Action potentials are responsible for signaling between plant cells and communication from the plants can be achieved through modulation of various parameters of the electrical signal in the plant tissue. The modulated signals are used for providing information to the microcontroller’s algorithm for working of the bio-machine. The changes of frequency of action potentials in plant are studied. Electromyography (EMG) electrodes and needle-type conductive electrodes along with electronic modules are used to collect and transform the information from the plant. Inverse fast Fourier transform (IFFT) is used to convert signal in frequency domain into voltage signal for real-time analysis. The changes in frequency of the plant action potentials to different light modes are used for the control of the bio-machine. This work has paved the way for an extensive research towards plant intelligence.